Determining Fractional Urate Excretion Rates in Hyponatremic Conditions and Improved Methods to Distinguish Cerebral/Renal Salt Wasting From the Syndrome of Inappropriate Secretion of Antidiuretic Hormone - Maesaka, John K.; Imbriano, Louis J.; Miyawaki, Nobuyuki (Frontiers in Medicine, 2018)
Our evaluation of hyponatremic patients is in a state of confusion because the assessment of the volume status of the patient and determinations of urine sodium concentrations (UNa) > 30-40 mEq/L have dominated our approach despite documented evidence of many shortcomings. Central to this confusion is our inability to differentiate cerebral/renal salt wasting (C/RSW) from the syndrome of inappropriate secretion of antidiuretic hormone (SIADH), syndromes with diametrically opposing therapeutic goals. The recent proposal to treat most or all hyponatremic patients makes differentiation even more important and reports of C/RSW occurring without cerebral disease lead to a clinically important proposal to change cerebral to renal salt wasting (RSW). Differentiating SIADH from RSW is difficult because of identical clinical parameters that characterize both syndromes. Determination of fractional urate excretion (FEurate) is central to a new algorithm, which has proven to be superior to current methods. We utilized this algorithm and differences in physiologic response to isotonic saline infusions between SIADH and RSW to evaluate hyponatremic patients from the general medical wards of the hospital. In 62 hyponatremic patients, 17 (27%) had SIADH, 19 (31%)a had reset osmostat (RO), 24 (38%) had RSW, 1 due to HCTZ and 1 Addison’s disease. Interestingly, 21 of 24 with RSW had no evidence of cerebral disease and 10 of 24 with RSW had UNa < 20 mEqL. We conclude that 1. RSW is much more common than is perceived, 2.the term cerebral salt wasting should be changed to RSW 3. RO should be eliminated as a subclass of SIADH, 4. SIADH should be redefined 5. the volume approach is ineffective and 6. There are limitations to determining UNa, plasma renin, aldosterone or atrial/brain natriuretic peptides. We also present data on a natriuretic peptide found in sera of patients with RSW and Alzheimer’s disease.